ROLE OF SERUM APOLIPOPROTEIN LEVELS IN INDIAN CHILDREN AND ADOLESCENTS. - DR. SRINIVASA NAGESWARA RAO.G; DR. PREMA GURUMURTHY; SRUTI.E (International Journal of Pharma and Bio Sciences, 2013)
The incidence of obesity among childhood in India is largely increasing. The serum apolipoproteins and its correlation with anthropometric and biochemical parameters were evaluated in 296 school children and adolescents (96 obese, 97 overweight, were compared with 103 normal controls, aged between 10-17 years). Anthropometric variables, lipid profile, fasting serum glucose analyzed by auto- analyzer and serum apolipoproteins by Immunoturbidimetry assay. Serum Apo-AI levels were decreased in obese and overweight children (130.94±9.24mg/dl, 132.26±10.80mg/dl Vs 153.08±17.98mg/dl) (p<0.001) than control children. Serum Apo-B levels were significantly elevated in obese and overweight children (88.54±11.4mg/dl, 82.6±12.64mg/dl Vs 73.55±12.03mg/dl) (p<0.001) than controls. Serum Apo-B levels showed positive correlation with BMI, WHR, Apo-B/Apo-AI ratio, TCHR, TC, TG, LDL-C and showed negative correlation with fasting glucose levels, and no association with HDL-C. Serum Apo-AI levels showed negative correlation with BMI, WHR, Apo-B/Apo-AI ratio, TCHR, TC, TG, LDL-C and showed positive correlation with HDL-C and fasting glucose levels. These findings suggest that childhood obesity is associated with abnormal lipid patterns. Prevention campaigns aimed at identifying obese children and reducing their weight would probably also improve the lipid profile.